Vegetable genetic resources : principles and management - Bhardwaj, D. R. (Daya Publishing House, 2021)
The present book has been written to fulfill the emergence of hue and cry for physical resources in the world which comprise land, water and the biological diversity. Management of landscapes for both production of food and conservation of ecosystem services and wild biodiversity forms the basis for eco-agriculture. In the regime of climate change, accelerated plant genetic resource collection, inventrization, PGR based technology development, assessment, refinement to maintain sustainability, issues related to framed rules, regulation and guidelines are focused in a comprehensive manner. In this book 16 chapters are well designed to cover origin, distribution, collection, evaluation, characterization, core set development, traditional approaches and most recent innovative (tissue culture, slow growth culture, cryo-techniques, molecular and biotechnological) protocols made to vegetable genetic diversity usable in breeding programme, setting trait specific goals for posterity and framing guideline suitable for Indian conditions. This book pertaining to vegetable genetic resources will be a milestone for stakeholders, policy makers, administrators, conservators, researchers, and teachers of India and abroad. It will cater to the needs of B.Sc. (Horticulture), B.Sc. (Agriculture), M.Sc. and Ph.D. (Vegetable Science) students. Collection to conservation methods have been elaborately dealt with, purposely to acquaint stakeholders to students with all aspects of vegetable genetic resources which is the backbone of vegetable crop improvement program. Glossary of important terms at the end is an added feature of this book.